2003
DOI: 10.1183/09031936.03.00061902
|View full text |Cite
|
Sign up to set email alerts
|

Slower rise of exhaled breath temperature in chronic obstructive pulmonary disease

Abstract: In chronic obstructive pulmonary disease (COPD) there is decreased vascularity of the bronchi and inflammation of the airways that may have opposite effects on the regulation of heat loss.Exhaled air temperature increase (DeuT) was measured in 23 patients with moderate COPD (18 male, mean age¡SEM 70¡1 yrs; forced expiratory volume in one second (FEV1) 45¡3%, FEV1/forced vital capacity 54¡4%) and 16 normal volunteers (64¡4 yr) and compared to exhaled nitric oxide (eNO) and inflammatory cells in induced sputum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
13
1
1
Order By: Relevance
“…Other studies found no association between exhaled breath temperature and age in children (age range: 9–11 years, n = 60) [30] and the exhaled air temperature was not statistically different in a relatively underpowered study of younger (20 ± 6 years, n = 8) compared to older (55 ± 9 years, n = 6) adults [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies found no association between exhaled breath temperature and age in children (age range: 9–11 years, n = 60) [30] and the exhaled air temperature was not statistically different in a relatively underpowered study of younger (20 ± 6 years, n = 8) compared to older (55 ± 9 years, n = 6) adults [31]. …”
Section: Discussionmentioning
confidence: 99%
“…There is a report that EBT is shifting downwards in patients with chronic obstructive pulmonary disease, in whom airways and pertaining vasculature are reduced [12]. We have preliminary yet unpublished data of increased EBT (but not axillary temperature) in cases with viral infections, tuberculosis and bronchopneumonia.…”
Section: Applicability Of the Ebt Device In Medicinementioning
confidence: 69%
“…Innes point out that we did not report the method of flow targeting. However, after describing the exhalation manoeuvre as flow and pressure controlled, we refer the reader to a previous publication by our group in which all the details related to the pressure (4 cmH 2 O) and flow control (visual feedback) are fully described (see reference [14] in the text of [1]). …”
Section: From the Authorsmentioning
confidence: 99%
“…Innes for their interest and constructive criticism relating to our paper which reported low exhaled breath temperature gradients in chronic obstructive pulmonary disease patients compared to normal subjects [1].…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation